REGULATION OF FUNCTIONAL FOODS IN UKRAINE AND THE WORLD. PROSPECTS FOR THE USE OF POSTBIOTICS AS FUNCTIONAL INGREDIENTS - A. Kapustian; N. Cherno; K. Naumenko; L. Gural; S. Osolina (Harčova Nauka ì Tehnologìâ, 2023)
Functional food allows to individualize the characteristics and necessities of each person. Over the past few decades, the demand for products that have a positive impact on human health has exploded worldwide. The market for functional foods in developed countries is estimated at USD 300 billion, which makes this sector attractive for investment. Accordingly, the production of functional foods and ingredients needs to be regulated at the state level. There is no harmonization in the definitions of functional foods and their classification at both the global and state levels. Despite the fact that the concept and terminology of functional food and the means of achieving it is well-established, the term “functional food” is often absent in the legislative acts of countries that actively produce functional foods, and the term “health-related food” is used instead. As a rule, health-related foods are subject to quality and safety requirements that are identical to those of conventional food products. Exceptions are regulations that establish rules for labeling FFPs and statements regarding their physiological effects or the content of a particular ingredient that may affect physiological aspects. In Europe and the USA, much attention is paid to the safety of “health-related food” and the novel food products. European Food Safety Authority and the US Food and Drug Administration require sponsors to submit information on the composition of multiple batches of a product to support safety evaluations for novel foods and Generally Recognized as Safe (GRAS) ingredients. In Ukraine, the legal status of the terms “functional food product” and dietary supplement was regulated by Law of Ukraine 771 “On Basic Principles and Requirements for Food Safety and Quality”, but in the version of this law dated 16.01.2020, this term was excluded, the term “dietary supplement” was edited and the term “novel food product or ingredient” was included, which is related to the process of harmonization of Ukrainian and European legislation in the food sector. In 2020, the Ministry of Health of Ukraine approved Order No. 1145 “On Approval of the Requirements for Nutrition Claims and Health Claims for Food Products”, which regulates the following concepts: claims and conditions for their use; health claims allowed to be used in food labeling and advertising, except for claims about reducing the risk of diseases and claims related to the development and health of children; claims about reducing the risk of diseases and claims related to the development and health of children. Unfortunately, Ukrainian regulations do not contain claims and conditions for the use of claims about pro- and prebiotics that have GRAS status worldwide. Particular attention should be paid to the possibility of using postbiotics as functional food ingredients with immunological activity.